The application of biogas fermentation digestate as soil fertilizer - Czakó-Vér, Klára; Somfai, Dávid; Suhajda, Erzsébet; Strasszer, Márk; Árvay, Gyula; Dolgosné Kovács, Anita; Dittrich, Ernő (Analecta Technica Szegedinensia, 2020)
As organic manure is becoming less available, using different materials as soil fertilizers and the application of the inorganic fertilizers raises many questions. Therefore, it is increasingly important to use compost and biogas digestate to improve soil quality. The activity of the microbial communities ensures the fertility of the soil. One of the most important enzymes is dehydrogenase. This enzyme group catalyses the hydrogen transfer in the process of biological oxidation. Our aim was to examine the effect of biogas digestate on dehydrogenase enzyme activity (DHA) in 3 different types of soil. Hungarian standard method was used to evaluate DHA. The applied biogas digestate was obtained from the Kaposvár Sugar Factory of Hungarian Sugar Ltd. The dose is equal to 16,7 m3ha-1 and 533 kg organic matterha-1. The treatment was performed in three different groups of soil: brown forest soil, calcareous chernozem and carbonate meadow soil. The results showed an increase in DHA in all types of soil. DHA values were the highest in case of the carbonate meadow soil, specifically 0.337 mg formazan/1 g soil/24 h immediately after the treatment and 0.410 after 28 days. A critical aspect to consider during the construction of biogas plants is the soil protection agency’s ban on using soil fertilizers during the winter months. Analysis carried out according to the protocol of sewage sludge examination revealed that biofermentate produced during biogas generation does not contain any environmentally harmful components. After the elaboration of a soil protection plan, the recommended way to apply biogas digestate to arable land is via injectors.